FLOW EXPERIENCE, CUSTOMER SATISFACTION, CUSTOMER EXPERIENCE, AND CUSTOMER LOYALTY ON ONLINE SHOPPING APPLICATIONS - Liestyana, Yuli; Hara, Muhammad (Jurnal Mebis, 2023)
The researchers wanted to get some evidence to prove the hypotheses of this study. Flow experience, customer satisfaction, customer experience, and customer loyalty are the variables in this study. From the population of online shopping application users in the Special Region of Yogyakarta, a sample was selected using a non-probability sampling technique with a purposive sampling method. The data was then analyzed using Partial Least Square with SmartPLS 3.0 software. The first testing stage is the outer measurement to obtain validity and reliability values. Then, the researchers conducted an inner model measurement to find evidence of whether the hypotheses were accepted or rejected. The analysis results show that (1) Flow experience has a positive effect on customer loyalty, (2) Flow experience has a positive effect on customer experience, (3) Customer experience has a positive effect on customer satisfaction, (4) Customer satisfaction does not have a positive effect on customer loyalty, (5) Customer experience has a positive effect on customer loyalty.